Take off in Japanese (Oxford : Oxford University Press, 2000)
Aimed at beginners or for those wishing to brush up their lost language skills, this structured cd's have 14 self-paced units provide instruction in Japanese from beginner to intermediate level. Recordings feature native speakers in everyday situations.
Keywords: Japanese language; Japanese language -- Conversation. Phrase books